"How does customer perception of salespeople influence the relationship? A study in an emerging economy". (May 2020) - Arditto, Luis; Cambra-Fierro, Jesús J.; Fuentes-Blasco, María; Jaraba, Ana Olavarría; Vázquez-Carrasco, Rosario
Abstract: Sales and sales force management is a complex activity that largely determines a company's commercial success. Customer perception of the salespeople in terms of expertise, trust, interaction, and risk can drive the establishment of long-lasting ties, making customer portfolio management profitable in the long-term. Yet to date, while much work has been done on company-customer relational issues, very few studies have taken customer perception of salespeople as their reference. Moreover, most existing studies have taken western countries and developed economies as their reference of analysis. The present study, in contrast, provides an analysis of an emerging economy context, Peru. Using a sample of more than 400 consumers and structural equations analysis, this article presents a model based on the Social Exchange Theory. The final part of the study presents the theoretical discussion together with key implications and recommendations for management.